2009
DOI: 10.1016/j.jcrs.2009.04.025
|View full text |Cite
|
Sign up to set email alerts
|

High-resolution optical coherence tomography visualization of LASIK flap displacement

Abstract: Uneventful myopic laser in situ keratomileusis (LASIK) was performed in both eyes of a 33-year-old woman. Two weeks after LASIK, examination of the left eye revealed flap striae radiating inferonasally from the superior hinge. The flap was relifted and repositioned to remove the irregular astigmatism and reduce the striae. Before the flap was relifted, Fourier-domain optical coherence tomography (FD-OCT) showed the gap at the temporal flap, which had not been detected by biomicroscopy. After the flap was relif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2010
2010
2025
2025

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 10 publications
1
8
0
Order By: Relevance
“…47 Further, AS-OCT has been used to measure the tear meniscus, 48 in anterior segment tumor imaging to differentiate cystic from solid lesions, 49 to assess the penetration of tumors, 50 and to monitor post-surgical patients. 51, 52 …”
Section: Resultsmentioning
confidence: 99%
“…47 Further, AS-OCT has been used to measure the tear meniscus, 48 in anterior segment tumor imaging to differentiate cystic from solid lesions, 49 to assess the penetration of tumors, 50 and to monitor post-surgical patients. 51, 52 …”
Section: Resultsmentioning
confidence: 99%
“…28 Therefore, Fourier-domain OCT may be better than time-domain OCT for evaluating the finer details of LASIK flaps. 29 We used the RTVue Fourier-domain OCT system to analyze flap thickness and found that the M2 microkeratome group had the greatest difference in central and periphery thickness. The IntraLase group (femtosecond group 1) and the VisuMax group (femtosecond group 2) had similar center-periphery differences.…”
Section: Discussionmentioning
confidence: 99%
“…High-resolution OCT is helpful in the visualization of flap thickness, flap interface (flap-stroma relationship), and flap displacement [ 24 ]. Reinstein et al [ 25 ] reported that the residual stromal thickness measured via OCT was thicker than that measured through very high-frequency ultrasound in many eyes with insufficient residual stromal thickness.…”
Section: Refractive Surgery and Ectatic Disordersmentioning
confidence: 99%